Insuficiencia renal y su repercusión en el estado emocional de una adulta mayor de 65 años de edad en la Unidad de Hemodiálisis del cantón Babahoyo - Lombeida Garcia, Stephany Katerine (2022)
In this research work a case study is developed, in which it is proposed to address a psychotherapeutic plan, focused on cognitive behavioral therapy, which is oriented with techniques developed for the therapeutic intervention of an older adult patient of 65 years of age, which through a thorough process was able to determine what kind of emotional affectations are generated by suffering from a chronic disease such as kidney failure, through which a qualitative approach is developed by applying psychological tools and techniques such as clinical observation, clinical history, direct interview, Hamilton anxiety test and Beck depression inventory, which benefited in the detection of specific signs and symptoms of a psychological disorder in order to achieve the establishment of a structural diagnosis, based on the detection of signs and symptoms of a psychological disorder in order to establish a structural diagnosis, clinical history, direct interview, Hamilton's anxiety test and Beck's depression inventory, which benefited in the detection of specific signs and symptoms of a psychological alteration in order to establish a structural diagnosis, based on the results obtained, coping strategies are proposed to help the patient to control or eliminate his automatic thoughts, elaborating a therapeutic scheme focused on obtaining favorable results in the progress of treatment execution.